Inconsistency of BDD reactivity assessed by ferri/ferro-cyanide redox system and electrocatalytic degradation capability. Issue 1 (31st December 2022) - Zhu, Ruitong; Liu, Fangmu; Deng, Zejun; Yu, Yuhang; Ma, Li; Long, Hangyu; Zhou, Kechao; Yu, Zhiming; Wei, Qiuping
Abstract: Ferri/ferro-cyanide ([Fe(CN)6 ] 3−/4− ) redox couple has been extensively used as a benchmark to assess electrocatalytic degradation capability of boron-doped diamond (BDD) electrodes. However, the [Fe(CN)6 ] 3−/4− is far more sensitive to the surface terminal groups of BDD surface than the other factors (e.g. surface morphology and electrode configuration) that are closely related to electrocatalytic degradation properties. Thus, inconsistency exists while correlating the degradation properties of BDD with electrochemical properties determined from ferri/ferro-cyanide redox couple. Herein, an exemplar pollutant, reactive blue 19 (RB-19), was electrochemically degraded using various terminated BDD electrodes, including hydrogen-terminated (H-BDD), oxygen-terminated (O-BDD) and porous oxygen-terminated BDDs (OE-BDD), obtained via cathodic and anodic polarization as well as oxygen plasma etching, respectively. Surprisingly, OE-BDD with the lower heterogeneous electron transfer rate constant for [Fe(CN)6 ] 3−/4− showed a better electrocatalytic degradation capability toward RB-19, indicating the inconsistency for qualitatively evaluating degradation properties according to the kinetic parameters extracted from [Fe(CN)6 ] 3−/4− redox system.